β–arrestin-2 regulation of the cAMP response element binding protein - Manson, Mary E (2011)
Previous work demonstrated that cystic fibrosis (CF) cells exhibit an increase in cAMP-mediated signaling as a characteristic response to lost CFTR function. Evidence for increased cAMP-mediated signaling in CF included increased phosphorylation of the cAMP response element binding protein (CREB) and elevated β-arrestin-2 (βarr2) expression. However, subsequent studies reveal that CREB activation in CF cells is independent of protein kinase- A (PKA). The goal of this study is to test the hypothesis that elevated βarr2 expression leads to increased CREB activation in a PKA-independent mechanism. βarr2-GFP expressing tracheal epithelial cells (βarr2-GFP) exhibit an increase of pCREB content and subsequent CRE activation compared to GFP expressing control cells. βarr2 activation of the ERK cascade represents a candidate mechanism leading to CREB activation. ERK exhibits increased activation in βarr2-GFP cells compared to cont-GFP cells and ERK inhibition diminishes CRE activation in both GFP and βarr2-GFP cells. To test directly whether CREB regulation in CF is βarr2-dependent, nasal epithelium excised from wt mice (Cftr +/+; βarr2 +/+), CF mice (Cftr −/−; βarr2 +/+), and DKO mice (Cftr −/−; βarr2 −/−) were analyzed for pCREB protein content. Removal of βarr2 expression from CF mice reduces both pCREB and pERK content to wt levels. These data indicate that CF-related CREB regulation is mediated directly through βarr2 expression via the ERK pathway.